The Influence of Managerial Ownership, Capital Structure, and Sustainability Report on Financial Performance in Food and Beverage Sub-Sector Companies Listed on The Indonesia Stock Exchange for The Period 2020-2024 - Adelina Febriani; Luh Dina Ekasari; Hendrik Suhendri (IRDH International Journal of Social Sciences & Humanities, 2026)
This study aims to analyze the effect of managerial ownership, capital structure, and the disclosure of Sustainability Reports on the financial performance of food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2020–2024. This study uses a quantitative approach with an explanatory research type to test causal relationships between variables. The data used are secondary data obtained from financial statements and company sustainability reports. The population of this study includes all manufacturing companies in the food and beverage sub-sector listed on the IDX for the period 2020–2024, with the sample determined using a purposive sampling method based on the criteria of companies with positive net income during the study period. The data analysis technique is conducted using multiple linear regression analysis accompanied by classical assumption tests, partial tests (t-tests), and simultaneous tests (F-tests). The research results show that managerial ownership does not have a significant effect on the company's financial performance. Capital structure, proxied by the Debt to Equity Ratio (DER), has a significant effect on the company's financial performance. In addition, the disclosure of the Sustainability Report also has a significant effect on the company's financial performance. Simultaneously, managerial ownership, capital structure, and Sustainability Report disclosure have a significant effect on the financial performance of companies in the food and beverage sub-sector. This study indicate that managerial ownership does not have a significant impact on the company’s financial performance, whereas capital structure, as measured by the Debt to Equity Ratio (DER), shows a significant influence on financial performance.